Approaches to modelling thermal diffuse scattering in triglycine sulfate, (NH2CH2COOH)3·H2SO4. (1st April 2014) - Hudspeth, J. M.; Goossens, D. J.; Welberry, T. R.
<x xml:space="preserve">Abstract</x> The thermal diffuse scattering in triglycine sulfate, (NH2CH2COOH)3·H2SO4, has been modelled by treating the intermolecular interactions that give rise to the correlated atomic displacements like Hooke's law springs. To limit the number of variables in the model, the force constants for the interactions were parameterized in a number of ways, the most successful of which was an empirical interaction potential using an exponential function of the interatomic separations.